A Provincial Survey of the Contemporary Management of Autosomal Dominant Polycystic Kidney Disease. (September 2020) - Yi, Tae Won; Levin, Adeera; Bevilacqua, Micheli; Canney, Mark
Background: Recent years have witnessed an encouraging expansion of knowledge and management tools in the care of patients with autosomal dominant polycystic kidney disease (ADPKD), including measurement of total kidney volume as a biomarker of disease progression, stringent blood pressure targets to slow cyst growth, and targeted treatments such as tolvaptan. Objectives: We sought to evaluate clinicians' familiarity with, and usage of, novel evidence-based management tools for ADPKD. Design: On-line survey. Setting: British Columbia, Canada. Participants: Nephrologists in academic and community practice (excluding clinicians who practice exclusively in transplantation). Measurements: Participants answered multiple-choice questions in 6 domains: sources of information, self-identified needs for optimal care delivery, prognostication, imaging tests, blood pressure targets, and use of tolvaptan. Methods: An online survey was developed and disseminated via email to 65 nephrologists engaged in current clinical practice in British Columbia. Results: A total of 29 nephrologists (45%) completed the questionnaire. The most popular source of information was the primary literature (83% of respondents). While 86% of respondents reported assessing the risk of disease progression before the onset of kidney function decline, most were using traditional metrics such as blood pressure and proteinuria rather than validated prediction tools such as the Mayo Classification. Although 90% of respondents obtained additional imaging after diagnosis in some or all of their ADPKD patients, only 1 in 5 reported being confident in their ability to interpret kidney size. The recommended blood pressure (BP) target of <110/75 mmHg was sought by 17% of respondents. All respondents reported being familiar with the literature regarding tolvaptan; however, only half were confident in their ability to identify suitable patients for treatment. The top 3 needs identified by clinicians were better access to medications (69%), clear management protocols (66%), and easier access to imaging tests (59%). Limitations: Funding mechanisms for tolvaptan can vary; therefore, clinicians' experience with the drug may not be generalizable. Although the response rate was acceptable, the survey is nonetheless subject to responder bias. Conclusion: This survey indicates that there is substantial variability in the usage of, and familiarity with, evidence-based ADPKD management tools among contemporary nephrologists, contributing to incomplete translation of evidence into clinical practice. Providing greater access to tolvaptan or imaging tests is unlikely to improve patient care without enhancing knowledge translation and education. Trial Registration: Not applicable as this was a survey.